2018
DOI: 10.1016/j.sjbs.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pH and butyric acid on butanol production during batch fermentation using a new local isolate of Clostridium acetobutylicum YM1

Abstract: The effect of pH and butyric acid supplementation on the production of butanol by a new local isolate of YM1 during batch culture fermentation was investigated. The results showed that pH had a significant effect on bacterial growth and butanol yield and productivity. The optimal initial pH that maximized butanol production was pH 6.0 ± 0.2. Controlled pH was found to be unsuitable for butanol production in strain YM1, while the uncontrolled pH condition with an initial pH of 6.0 ± 0.2 was suitable for bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 38 publications
4
23
0
3
Order By: Relevance
“…Although the biobutanol yield in SSF is slightly lower than SHF, SSF could still provide a better productivity than SHF besides its advantages in reducing the number of steps, time, and apparatus . The initial pH was set at pH 5.5 based on previous studies . The pH was dropped to 4.9 after 24 hour of fermentation due to the formation of acids indicating the acidogenic phase of the ABE fermentation and slightly increased during the solventogenic phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the biobutanol yield in SSF is slightly lower than SHF, SSF could still provide a better productivity than SHF besides its advantages in reducing the number of steps, time, and apparatus . The initial pH was set at pH 5.5 based on previous studies . The pH was dropped to 4.9 after 24 hour of fermentation due to the formation of acids indicating the acidogenic phase of the ABE fermentation and slightly increased during the solventogenic phase.…”
Section: Resultsmentioning
confidence: 99%
“…11 The initial pH was set at pH 5.5 based on previous studies. 11,53,54 The pH was dropped to 4.9 after 24 hour of fermentation due to the formation of acids indicating the acidogenic phase of the ABE fermentation and slightly increased during the solventogenic phase.…”
Section: Simultaneous Saccharification and Fermentationmentioning
confidence: 99%
“…27 A critical point is the pH because it has been seen that it is related to the production and yield in the solventogenic phase of the ABE fermentation. Therefore, according to Al-Shorgani et al, 28 the pH should range between 5.0 and 6.5, and at pH 6.0 it has shown that the concentration of H+ ion remains within the physiological range, which prevents sporulation and allows the generation of butanol. 17 Of the five native isolates of Clostridium, strains C9FD1, C3FD11, and C14FY8 produced butanol, (data shown in Table 5).…”
Section: Production Of Butanol With Synthetic P2 Medium and Chwmentioning
confidence: 99%
“…The reduction of pH demonstrates that hydrogen production occurred in the fermentation process. However, the decrease in low pH would greatly inhibit the metabolism of bacterial growth and cause a decrease in hydrogen production [52].…”
Section: Hydrogen Productionmentioning
confidence: 99%
“…On the other hand, fermentation at initial pH 7 and any concentration or temperature can produce VFAs with higher yield. However, the decrease in low pH would greatly inhibit the metabolism of bacterial growth and cause a decrease in hydrogen production [52].…”
Section: Butyric Acid Productionmentioning
confidence: 99%